Improving Media Literacy Among Higher Education Students Through Vitagenic Information - Darmonjon Maxmudova; Egambergan Khudoynazarov; Meruert Pazilova; Khairulla Alyaminov; Gulbahar Abilova; Zamira Sherimbetova; Sherzod Korabayev (Qubahan Academic Journal)
This research investigates the influence of vitagenic information on enhancing media literacy among students in higher education. The primary focus is on how students can leverage their personal experiences and vitagenic learning to critically assess and interact with a wide array of media content in the current digital landscape. Background. As digital media and information become increasingly prevalent, students in higher education regularly encounter a significant volume of content that necessitates advanced critical evaluation skills. Vitagenic information, which refers to life experiences and practical knowledge, is essential in developing students' media literacy. By incorporating vitagenic learning, students gain the ability to discern credible information from misinformation, thereby improving their media engagement. Research Methods. The study employs a mixed-methods methodology, integrating both qualitative and quantitative data. Surveys were conducted with 200 university students to evaluate their existing media literacy levels and to determine how vitagenic experiences affect their critical thinking abilities. Additionally, focus groups were organized to collect detailed insights into how students utilize their vitagenic knowledge when consuming media. Results. Initial findings reveal a noteworthy relationship between students' personal experiences and their capacity for media analysis. Students with a robust background in vitagenic learning tend to achieve higher media literacy scores, especially in identifying biased or misleading content. Conclusion. The study's results indicate that incorporating vitagenic information into the curricula of higher education institutions could significantly bolster students' media literacy competencies. This method allows students to draw on their practical knowledge and life experiences, leading to more informed and critical interactions with digital media.